2017
DOI: 10.4103/iju.iju_418_16
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional versus two-dimensional laparoscopy in urology: A randomized study

Abstract: Introduction:Conventional two-dimensional (2D) laparoscopy systems have the drawback of poor depth perception and spatial orientation. Three-dimensional (3D) laparoscopic systems have stereoscopic vision in which depth perception is achieved by different unique images received by each eye. We evaluated 3D laparoscopy in comparison with conventional 2D laparoscopy in urological procedures in a prospective randomized study.Materials and Methods:Over a 19 month study period, 108 patients scheduled to undergo vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 11 publications
0
30
0
2
Order By: Relevance
“…Three studies 16 , 24 , 31 compared 2D and 3D laparoscopic systems during the pyeloplasty procedure (53 vs 45 patients, respectively). Of all the parameters reported in these studies, only operative time and EBL were comparable for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 16 , 24 , 31 compared 2D and 3D laparoscopic systems during the pyeloplasty procedure (53 vs 45 patients, respectively). Of all the parameters reported in these studies, only operative time and EBL were comparable for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…12 The most commonly used 3D imaging systems were the Karl Storz FULL HD 3D System (Karl Storz GmbH & Co. KG, Tüttlingen, Germany) [13][14][15][16][17][18][19][20][21] and the Viking 3D HD Laparoscopic Vision System (Viking Systems, Inc., La Jolla, CA). [22][23][24][25][26][27][28][29][30] Additionally, the Einstein Vision 3D (Schoelly-Fibreoptic GMBH, Germany) was used in some studies. 31,32 Others, such as McDougall et al, conducted their studies with the Endolive Stereo Endoscope (Carl Zeiss, Oberkochen, Germany) and the StereoVu Video Laparoscopen (Welch Allyn Surgical Imaging Systems, Skaneateles Falls, NY) systems.…”
Section: Resultsmentioning
confidence: 99%
“…The time required to complete the critical steps during adrenalectomy, nephron-sparing nephrectomy, radical and simple nephrectomy, pyeloplasty, and ureterolithotomy was shortened using 3D vision. 13 Furthermore, a reduction in dissection time was reported for simple nephrectomy 23 and pyeloplasty 19,23 when using 3D vision systems. The efficiency score for pyeloplasty and partial nephrectomy was better using 3D imaging compared with conventional 2D technology.…”
Section: Surgery Timementioning
confidence: 99%
“…This randomized study included 108 patients in each of the two arms: two-dimensional and 3-D laparoscopy. [ 6 ] The authors evaluated a number of surgical parameters and outcomes and concluded that depth perception allows improvement in operative time and lowers the surgeon's stress.…”
Section: Three-dimensional Laparoscopymentioning
confidence: 99%